2023
DOI: 10.3389/fnhum.2023.1177594
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of repetitive transcranial magnetic stimulation on cognitive impairment in stroke patients: a systematic review and meta-analysis

Abstract: BackgroundIn recent years, repetitive transcranial magnetic stimulation (rTMS) has emerged as a noninvasive and painless treatment for post-stroke cognitive impairment (PSCI). However, few studies have analyzed the intervention parameters of cognitive function and the effectiveness and safety of rTMS for treating patients with PSCI. Thus, this meta-analysis aimed to analyze the interventional parameters of rTMS and evaluate the safety and effectiveness of rTMS for treating patients with PSCI.MethodsAccording t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…MMSE, MoCA, BI, MBI, RBMT, and LOTCA were among the primary outcome indicators used. Thirteen ( 31–41 , 43 , 47 ) articles reported financial support. Most studies concluded that rTMS has advantages in treating PSCI but emphasized the need for more, higher-quality studies to validate the results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…MMSE, MoCA, BI, MBI, RBMT, and LOTCA were among the primary outcome indicators used. Thirteen ( 31–41 , 43 , 47 ) articles reported financial support. Most studies concluded that rTMS has advantages in treating PSCI but emphasized the need for more, higher-quality studies to validate the results.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the literature rankings published in 2023 were positioned as 17. The earliest publication date is 2021, containing five ( 31 , 33 , 34 , 42 , 46 ) studies; the latest is 2023, containing 10 ( 32 , 36–40 , 43–45 , 47 ). Meanwhile, there were two ( 35 , 41 ) studies in 2022.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations